Smooth muscle cell specific ablation of CXCL12 downregulates endothelial CXCR7 leading to defective coronary arteries and cardiac hypertrophy. (14th October 2021) - Messner, M; Ghadge, S K; Seiringer, H; Maurer, T; Staggl, S; Zeller, T; Mueller, C; Wenninger, W J; Geyer, S H; Sopper, S; Krogsdam, A; Poelzl, G; et al.
Abstract: Aims: The chemokine CXCL12 plays a fundamental role in cardiovascular development, cell trafficking, and myocardial repair. Human genome-wide association studies even have identified novel loci downstream of the CXCL12 gene locus associated with coronary artery disease and myocardial infarction. Nevertheless, cell and tissue specific effects of CXCL12 are barely understood. Since we detected high expression of CXCL12 in smooth muscle (SM) cells, we generated a SM22-alpha-Cre driven mouse model to ablate CXCL12 (SM-CXCL12−/−). Methods and results: SM-CXCL12−/− mice revealed high embryonic lethality (50%) with developmental defects, including aberrant topology of coronary arteries. Postnatally, SM-CXCL12−/− mice developed severe cardiac hypertrophy associated with fibrosis, apoptotic cell death, impaired heart function, and severe coronary vascular defects characterized by thinned and dilated arteries. Transcriptome analyses showed specific upregulation of pathways associated with hypertrophic cardiomyopathy, collagen protein network, heart-related proteoglycans, and downregulation of the M2 macrophage modulators. CXCL12 mutants showed endothelial downregulation of the CXCL12 co-receptor CXCR7. Treatment of SM-CXCL12−/− mice with the CXCR7 agonist TC14012 attenuated cardiac hypertrophy associated with increased pERK signaling. Conclusion: Our data suggest a critical role of smooth muscle-specific CXCL12 in arterial development, vessel maturation, and cardiac hypertrophy. Pharmacological stimulation of CXCR7 might be a promising target to attenuate adverse hypertrophic remodeling. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FWF-Austria